Justice in Transition: The Effectiveness of Restorative Justice in Resolving Social Conflicts - Shodiq, Md; Sumaryanto, A. Djoko (Jurnal Hukum dan Keadilan, 2025)
This study analyzes the effectiveness of implementing restorative justice in resolving social conflicts within Indonesian communities as part of the transitional justice process. Using a qualitative approach and a case study method in several regions such as Poso, North Maluku, and West Sumatra this research explores how restorative mechanisms rooted in local wisdom can restore social relations, strengthen community cohesion, and prevent recurring conflicts. The findings reveal that restorative justice approaches are effective in fostering reconciliation at the community level through dialogue, acknowledgment of wrongdoing, and traditional symbolic acts. However, their effectiveness largely depends on institutional support, facilitator capacity, and the alignment of public policies. The integration of local values such as musyawarah (deliberation), pela gandong, and alek nagari emerges as a key factor in sustaining the peacebuilding process. These findings emphasize the importance of strengthening the national legal framework, engaging civil society, and enhancing the capacity of local actors so that restorative justice can function not only as a conflict resolution mechanism but also as a means of achieving long-term social transformation